Developing an Ultrasensitive Silicon Nanowire based ISFET Biosensor to Identify Dengue Fever Early - Patnala, Tulasi Radhika; Tatineni, Madhavi (Journal of Neonatal Surgery, 2025)
Dengue fever is a swiftly proliferating mosquito-transmitted viral illness that presents a considerable global health issue, especially in tropical and subtropical areas. Present diagnostic methods, such as ELISA and RT-PCR, exhibit constraints regarding speed, cost, and sensitivity, highlighting the need for innovative biosensing technologies aimed at facilitating early detection. This investigation delves into the creation of an ultrasensitive, label-free Silicon Nanowire based ion sensitive Field-Effect Transistor (SiNW based ISFET) biosensor aimed at the early detection of the Dengue virus (DENV). The proposed biosensor aims to identify DENV at very low concentrations in human blood samples, enabling swift diagnosis and prompt medical action. The performance of the sensor is assessed via simulation with the COMSOL semiconductor module, focusing on critical parameters including sensitivity, specificity, and limit of detection (LOD). The findings indicate that the SiNW based ISFET biosensor shows significant potential for high-precision DENV detection, presenting a promising alternative to traditional diagnostic methods. This study advances biosensing technology and demonstrates the practicality of SiNW-based ISFET for point-of-care applications, potentially enhancing dengue fever management and minimizing severe complications linked to delayed diagnosis.